Cleaning Robot with Android Application Controller - Sinnapatchai, Devabalan; Mohd Zaini, Nur Ellysa Mu'izz; Mohd salleh, Nur Syahira; Md Som, Mohamad (Multidisciplinary Applied Research and Innovation, 2022)
This research aims to discuss the development of cleaning robot using Arduino and Android application controller. Robot vacuum cleaners were developed to make cleaning easier, rather than using handheld vacuum cleaners including dry cleaning, wet cleaning and dust collection. Then send the output to the Arduino which controls the movement of the cleaning robot. In order to facilitate the execution of certain functions, interactivity plays an important role together with the binary signal sent to the robot via Bluetooth. In this research, a robot vacuum cleaner with an intelligent interface was developed. With the help of the HC05 Bluetooth module, users can use Android smartphones to control their sports remotely. There are two functions: dry cleaning mode and dry cleaning mode. Both wet cleaning modes work when the user turns on the robot to control its movements via the Android app on the smartphone. As a result, a prototype of the robot was manufactured and tested.